Ketogenic diets and β-hydroxybutyrate in the prevention and treatment of diabetic kidney disease: current progress and future perspectives - Li, Junle; He, Wanhong; Wu, Qianshi; Qin, Yuanyuan; Luo, Changfang; Dai, Zhuojun; Long, Yang; Yan, Pijun; Huang, Wei; Cao, Ling (BMC nephrology, 2025)
Diabetic kidney disease (DKD) is the main cause of end-stage renal disease. Ketogenic diets (KD) is a high-fat, low-carbohydrate diet. KD produces ketone bodies to supplement energy in the case of insufficient glucose in the body. β-Hydroxybutyrate (BHB) is the main component of ketone bodies. BHB serves as "ancillary fuel" substituting (but also inducing) anti-oxidative, anti-inflammatory, and cardio-protective features by binding to several target proteins, including histone acylation modification, or G protein-coupled receptors (GPCRs). KD have been used to treat epilepsy, obesity, type-2 diabetes mellitus, polycystic ovary syndrome, cancers, and other diseases. According to recent research, KD and the induced BHB delay DKD progression by improving the metabolism of glucose and lipids, regulating autophagy, as well as alleviating inflammation, oxidative stress and fibrosis. However, due to some side-effects, the role and mechanism of action of KD and BHB in the prevention and treatment of DKD are controversial. This review focuses on recent progress in the research of KD and BHB in clinical and preclinical studies of DKD, and provides new perspectives for DKD treatment.